2019
DOI: 10.1158/1940-6207.capr-18-0221
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of 92 Serum Protein Biomarkers for the Development of a Multiprotein Classifier for Ovarian Cancer Detection

Abstract: The best known ovarian cancer biomarker, CA125, is neither adequately sensitive nor specific for screening the general population. By using a combination of proteins for screening, it may be possible to increase the sensitivity and specificity over CA125 alone. In this study, we used Proseek Multiplex Oncology II plates to simultaneously measure the expression of 92 cancer-related proteins in serum using proximity extension assays. This technology combines the sensitivity of the PCR with the specificity of ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…their recent study on 92 biomarkers (Olink's Oncology II panel) reported lower levels of ITGAV in serum from ovarian cancer patients compared to healthy women [34].…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…their recent study on 92 biomarkers (Olink's Oncology II panel) reported lower levels of ITGAV in serum from ovarian cancer patients compared to healthy women [34].…”
Section: Plos Onementioning
confidence: 98%
“…In recent years, proximity extension assay (PEA) technology has been employed in the identification of novel protein biomarkers and biomarker combinations for early detection of ovarian cancer, with promising results [34,[48][49][50]. The addition of inflammatory and immunological biomarkers to CA125 and HE4 holds potential to increase sensitivity and specificity compared to the established algorithms.…”
Section: Biomarkers For Ovarian Cancer Detectionmentioning
confidence: 99%
“…Recently, Skubitz and group (Skubitz et al., 2019) has studied on multi-biomarkers that can differentiate between the serum samples of late stage high grade serous ovarian cancer and healthy control based on Proseek® Multiplex Oncology II plates. This plate can simultaneously measure the expression of 92 cancer related serum based protein biomarkers using proximity extension assays (PEA) (Assarsson et al., 2014; Thorsen et al., 2013; Chen et al., 2015).…”
Section: Other Advanced Approaches For Early Diagnosis Of Ovarian Cancermentioning
confidence: 99%
“…In addition, to meet the minimum screening criteria of 99.6 % specificity, CA125 achieved a sensitivity of 85 %. Further, five biomarkers including FGFBP1, S100A4, EGF, ICOSLG, and MSLN, which were otherwise found at lower level with respect to control, on combination with CA125 enhances the sensitivity and specificity (Skubitz et al., 2019). This perhaps supports the inverse correlation study of additional biomarkers to primary markers (Pinsky and Zhu, 2011).…”
Section: Other Advanced Approaches For Early Diagnosis Of Ovarian Cancermentioning
confidence: 99%
“…Future clinical applications may include ELISA tests using Pap test fluid or cervical swabs as the diagnostic biospecimen, or multiplexed proximity extension assays could be developed for use on Pap tests to sensitively quantify multiple proteins of interest [ 49 , 50 ]. Alternatively, SRM-based targeted proteomic assays are increasingly being used in the measurement of clinically significant proteins, allowing for cost effective, high throughput, sensitive, robust, multiplexed analysis and quantification [ 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%